2018
DOI: 10.1016/j.techfore.2017.04.023
|View full text |Cite
|
Sign up to set email alerts
|

The Internet of Things, dynamic data and information processing capabilities, and operational agility

Abstract: Whilst there are promising links between the Internet of Things (IoTs), dynamic data and information processing capabilities (DDIPCs), and operational agility, scholars have not conducted enough empirical studies that offer convincing evidence for the use of the IoTs and relevant linkages. This study therefore examines the links between such constructs and provides managerial implications for contemporary data and information driven managers who adopt evidence-based decision making for better operational outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
78
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(83 citation statements)
references
References 78 publications
(190 reference statements)
4
78
0
1
Order By: Relevance
“…Emphasis is also placed on the important role played by IoTs in operational agility, indicating the need for managers to invest in such destructive technologies and to improve the IT organizational infrastructure of their enterprises, in order to take advantage of a large amount of data and information through devices connected to the Internet to develop operational agility and manufacturing scalability (Akhtar et al, 2017).…”
Section: Inferential Statistics (Chi-square and Spearman's Correlatiomentioning
confidence: 99%
See 1 more Smart Citation
“…Emphasis is also placed on the important role played by IoTs in operational agility, indicating the need for managers to invest in such destructive technologies and to improve the IT organizational infrastructure of their enterprises, in order to take advantage of a large amount of data and information through devices connected to the Internet to develop operational agility and manufacturing scalability (Akhtar et al, 2017).…”
Section: Inferential Statistics (Chi-square and Spearman's Correlatiomentioning
confidence: 99%
“…This may suggest that organizations have already begun to understand the relationship between Big Data and AI techniques. For Akhtar et al (2017), today's business operations are flooded with structured and unstructured data, and modern companies can rely on new tools and techniques to process data and share information, and expert systems of artificial intelligence can provide their data mining tools and learning tools of machines for the conversion of information into knowledge (Gubbi et al, 2013;Pan, 2016).…”
Section: Inferential Statistics (Chi-square and Spearman's Correlatiomentioning
confidence: 99%
“…All of which can be controlled wirelessly via phones, computers, microphones (e.g., Amazon Echo or Google Home), and other inputs. Within dynamic and competitive environments, recent research found that IoT supports the productivity of business processes with regards to building dynamic data and information processing capabilities, and enhancing organizational and operational agility [45]. We can conclude that the IoT is an intelligent connection among all machines through the internet.…”
Section: Internet Of Things (Iot)mentioning
confidence: 78%
“…The European Commission Information Society similarly defined the IoT as "Interconnected objects having an active role in what might be called the Future Internet" (Pang, et al, 2015). The value of an IoT based TSS resides in the data or information (Akhtar, 2017) which is derived from sensors with edge intelligence capabilities or streamed data forming the bases of many service products. The potentially disruptive IoT based TSS technology can enable products that have the potential to generate innovations that have global impact (Miranda, et al, 2012), and can form the backbone for Industry 4.0 (Bauer et al, 2015).…”
Section: Trillion Sensor Based Iot Infrastructurementioning
confidence: 99%